2016
DOI: 10.7150/thno.13944
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulating the Size and Cargo of Tumor Exosomes in a Tissue-Engineered Model

Abstract: There is a growing interest in the pivotal role of exosomes in cancer and in their use as biomarkers. However, despite the importance of the microenvironment for cancer initiation and progression, monolayer cultures of tumor cells still represent the main in vitro source of exosomes. As a result, their environmental regulation remains largely unknown. Here, we report a three-dimensional tumor model for studying exosomes, using Ewing's sarcoma type 1 as a clinically relevant example. The bioengineered model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 55 publications
9
76
1
Order By: Relevance
“…The harvested EVs showed typical round, cup shape via SEM imaging in both 2D and 3D culture conditions (Figure 2 B and D), while 3D culture-derived EVs showed the more dense distribution of smaller size. These observations were in agreement with Rocha, et al that exosomes released by tissue-engineered tumors were smaller than exosomes released by the same cells cultured in monolayer, and the 3D system is more active for producing exosomes 56,57 . It is interesting that our observation is the same as Rocha, et al report that the maximum period for conditioned media collection was 48 h for 2D.…”
Section: Ev Secretion Dynamics From 3d Cultured Cells Significantly Dsupporting
confidence: 92%
See 1 more Smart Citation
“…The harvested EVs showed typical round, cup shape via SEM imaging in both 2D and 3D culture conditions (Figure 2 B and D), while 3D culture-derived EVs showed the more dense distribution of smaller size. These observations were in agreement with Rocha, et al that exosomes released by tissue-engineered tumors were smaller than exosomes released by the same cells cultured in monolayer, and the 3D system is more active for producing exosomes 56,57 . It is interesting that our observation is the same as Rocha, et al report that the maximum period for conditioned media collection was 48 h for 2D.…”
Section: Ev Secretion Dynamics From 3d Cultured Cells Significantly Dsupporting
confidence: 92%
“…More importantly, we observed that 3D cell-derived EV sample was clustered together with two in vivo cervical cancer patient plasma sample derived EV miRNAs. It supports that 3D cell culture is necessary for reproducing the EV miRNA content sorted by in vivo cells and establishing an accurate disease model 57,58 . On the other hand, the 2D-derived samples were clustered away from the in vivo samples, indicating that 2D cell culture was unable to represent in vivo biological status.…”
Section: The 3d Cell Culture Derived Ev Rna Profile Shows a Significasupporting
confidence: 56%
“…2019, 6, 1800948 Figure 1. [52] As EV preparations were enriched in small-sized vesicles corresponding to the size of exosomes, [64] we tested the expression of exosome markers CD9, Flotillin-1, and CD81 (Cytochrome cas a negative control) by imaging flow cytometry (Figure 3e,f; Figure S2, Supporting Information). Conditioned medium (CM) isolated after 6 d of 3D cell culture and 2 d of 2D cell culture was used for EV isolation by differential centrifugation.…”
Section: D Cellular Architecture Favors the Release Of Smaller Evs Ementioning
confidence: 99%
“…In the last few years, 3D in vitro models have been developed and tailored to better recapitulate the in vivo features of tumors. [50][51][52] Additionally, it is unclear whether 3D models provide an efficient and costeffective production of EVs as compared to 2D models. [46] Importantly, it has already been shown that some of these cellular features, such as differentiation [47] and phenotype, [48,49] affect the content and function of EVs.…”
Section: Introductionmentioning
confidence: 99%
“…One class of EVs is the Exos, “inward‐budding” vesicles that are generated in MVBs and secreted when the MVBs fuse with the cytomembrane 55, 56. The biogenesis and release of Exos is a complex symphony involving a series of factors, representatively including the endosomal sorting complexes required for transport (ESCRT), ALIX (also known as programed cell death 6‐interacting protein), phospholipase, vacuolar protein sorting‐associated 4 (VPS4), Rab GTPase proteins, sphingomyelinase, and ceramide 57, 58, 59…”
Section: Biogenesis and Release Of Evsmentioning
confidence: 99%